Maligaya sana ang Pasko - Lazaro, Cheche (Quezon City Probe Productions, 1992)
The making of the MTV of the song "Maligaya sana ang Pasko" from the people that had the idea to the mssage and the signers sentiments. Traces the beginning, provincial background and the reactions to the first trip to Manila of a group of young boys from Bukidnon perform at the CCP. Show the carnivals in Metro Manila.
Maligaya sana ang Pasko (17 min.) -- Benedictine's Choir Boys (16 min.) -- Christmas fairs and carnivals (14 min.)
VHS.
Keywords: Benedictine Boys Choir (Bukidnon); Music, Philippine; Christmas -- Philippines; Carnivals -- Philippines -- Manila metropolitan area